A robust enzymeless glucose sensor based on CuO nanoseed modified electrodes. Issue 28 (28th July 2015) - Ahmad, Rafiq; Tripathy, Nirmalya; Hahn, Yoon-Bong; Umar, Ahmad; Ibrahim, Ahmed A.; Kim, S. H.
<x xml:space="preserve">Abstract</x> CuO nanoseeds were synthesized via a low-temperature aqueous route, for the fabrication of a robust enzymeless glucose sensor.